Analysis of the Influence of Experience, Psychological Empowerment, and Career Development on Employee Commitment in Fintech Industry - Djunaedi Djunaedi; Tyahya Whisnu Hendratni; Titis Nistia Sari; Daniel Joseph Benedict Ngamelubun; Mohammad Azharie Hamdany; Roy Setiawan (Journal of Innovative and Creativity, 2025)
This study aims to examine how work experience, psychological empowerment, and career development influence the level of employee commitment in the fintech industry. Using a quantitative approach and survey method, the study involved 300 respondents selected purposively based on specific criteria, such as having a minimum of one year of work experience and participation in company-provided career development programs. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The results show that all three independent variables, work experience, psychological empowerment, and career development have a positive and significant impact on employee commitment. Work experience helps employees understand organizational dynamics and values, thereby strengthening their loyalty. Psychological empowerment promotes higher motivation, a sense of belonging, and greater engagement in work. Meanwhile, career development opportunities provide a positive outlook on the future and foster stronger emotional ties between employees and the organization. These findings highlight the importance for fintech companies to actively create a work environment that supports psychological empowerment, offers clear career pathways, and leverages employee experience as an asset to enhance engagement. Practically, this study offers guidance for HR management in designing policies that strengthen employee loyalty, and theoretically, it enriches the academic literature on the factors influencing employee commitment in the financial technology sector.